Piano Competitions in the Socio-Cultural Realities of Globalization - Berehova, Olena; Volkov, Sergii (Journal of History Culture and Art Research, 2019)
This article investigates the impact of globalization on music culture, in particular, on international piano competitions. New forms of interaction between the artist and the listener are emphasized, such as online broadcasting of music events, their advertising on social networks, presentation of video and audio recordings of concerts on personal or specially created pages of social networks, and specialized Internet platforms, etc. One of the most serious problems in the development of music culture in the context of globalization, the authors consider the problem of the selection, reliability, and quality of information, which leads to the demand for reputable consultants in the field of music information. The emphasis is placed on the role of international music organizations, which play an important integrating role in the processes of international artistic exchange and at the same time is a prestigious field of demonstration of the best artistic and the creative achievements of national cultures. Based on a study of information materials from more than 40 international piano competitions, authors have proposed their classification according to concepts and revealed global trends in the development of piano competitions. It is proved that competitive movement in the field of piano performance is clear evidence of the phenomenon of globalization, that is, the simultaneous influence of global and local cultural and artistic processes. Ways of implementing the idea of creating and performing new music in the framework of piano competitions have been identified. Specific examples of international music festivals and other artistic projects that include piano competitions or at their own initiative show that competitions promote the development and promotion of the cultural identity of countries at the global level help to spread music performance in the world and are one of the most popular cultural diplomacy.